2007
DOI: 10.2320/matertrans.48.560
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Hydrogen Isotope Absorption for Well-Annealed Palladium-Platinum Alloys

Abstract: Absorption kinetics of protium and deuterium for Pd, Pd-4 at%Pt and Pd-8 at%Pt were studied in a dilute hydrogen concentration region in a temperature region from 274 to 357 K by means of constant volume method, where samples were annealed well at 973 K under vacuum before measurements to remove defects induced by sample preparation. It was found that protium had larger rate constants for adsorption, lower rate constants for desorption and larger diffusion constants than those of deuterium within the examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The £-MgH 2 phase is known to form when the ¢-phase is subjected to compressive pressure in the 2.58 GPa range. 22,23) The H- The hydrogen consumption behavior in the dehydrogenated sample, Mg/5 mass%Nb 2 O 5 at ³5 MPa hydrogen atmosphere, is shown in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The £-MgH 2 phase is known to form when the ¢-phase is subjected to compressive pressure in the 2.58 GPa range. 22,23) The H- The hydrogen consumption behavior in the dehydrogenated sample, Mg/5 mass%Nb 2 O 5 at ³5 MPa hydrogen atmosphere, is shown in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that the activation energy for hydrogen absorption was almost zero for Pd with 4 mass% Pt below 100°C. 22) Here we attempted to analyze the hydrogen absorption kinetics of Mg with Nb 2 O 5 by measuring the hydrogen consumption behavior in a closed chamber as a function of time and temperature, and evaluate the apparent activation energy for hydrogenation. The hydrogen consumption behaviors were categorized into two types based on their consumption kinetic processes: increasing consumption rate with temperature at lower temperatures and almost constant consumption rate at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen absorption and desorption using metal hydrides have been widely investigated for hydrogen storage, purification, and isotopic separation due to their high storage capacities and moderate desorption temperatures and pressures. (1)(2)(3)(4) Additionally, the various hydrogen isotopes (tritium (T), deuterium (D) and protium (P)), have many applications in the medical field, nuclear energy, and defense missions. (5-7) Deuterium (D2), one of the hydrogen's stable isotopes, is widely used in fission reactors, neutron scattering and as an isotope tracking marker in numerous chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…(10) The interaction energies of the lighter hydrogen isotopes are weaker than the heavier isotopes because of the higher energies of the quantum states. (25,26) Furthermore, the thermal de Broglie wavelength increases as the temperature and molecular mass are lowered. Ultimately, this speeds up the overall gas release process.…”
Section: Introductionmentioning
confidence: 99%